Phong pioneers: exploring the sociopolitics of mythology in upland Laos - Tappe, Oliver (Social anthropology, 2021)
Hat Ang, mythological culture hero of the Phong (an ethnic minority in Laos), exemplifies the figure of the upland pioneer. Taking the legend of Hat Ang as a vantage point, this paper discusses the ethnohistory of this specific Austroasiatic group and offers a mythological perspective into the discussion of uplanders’ agency and future-making. This key myth of the Phong addresses questions of remoteness and relationality, of individual aspirations and hubris. Therefore, investigating mythology is key to understanding past and present representations of Phong culture and society within a multi-ethnic upland context.
Gesehen am 11.11.2021